Impact of early weaning on small intestine, metabolic, immune and endocrine system development, growth and body composition in artificially reared lambs. (26th November 2019) - McCoard, Sue A; Cristobal-Carballo, Omar; Knol, Frederik W; Heiser, Axel; Khan, Muhammed A; Hennes, Nina; Johnstone, Peter; Lewis, Sarah; Stevens, David R
Abstract: AbstractThis study evaluated the effect of early weaning (EW ) of artificially reared lambs using a restricted milk replacer (MR ) feeding and step-down weaning system on the short- and long-term effects on growth, feed intake, selected blood metabolites and hormones, body composition, and small intestine development. Mixed-sex twin-born 2 to 5 d old lambs were randomly allocated to individual pens and fed MR at 20% of initial individual BW in week 1 and 15% in week 2 followed by weaning off MR by the end of week 4 (EW; n = 16) or week 6 (Control; Ctrl, n = 16) using a step-down procedure. Concentrate starter and fiber diets were offered ad libitum to week 9, then gradually removed over a 10-d period. All lambs were managed as a single group on pasture from weeks 6 to 16 of the trial. Feed intake was recorded daily in the first 6 wk, and BWs recorded weekly. At weeks 2, 4, 6, and 8, and pre- and postclostridial vaccination at week 8, blood samples were collected for analysis of selected blood metabolites, IGF-1, and immune function. Body composition was evaluated in eight animals per group at weeks 4 and 16 after euthanasia, and duodenal samples collected for histomorphometric evaluation. Early weaned lambs had lower DM, ME, CP, and NDF intake than Ctrl lambs at 21, 15, 21, and 36 d of rearing, respectively ( P < 0.001), driven by lower intakes of MR from day 15 ( P < 0.001) as per the experimental design, and lower total DMI of fiber ( P = 0.001) from 21 to 42 d of rearing. Lamb BW tended ( P = 0.097) to be lower in EW than Ctrl lambs from 5 to 10 wk of rearing, with lower ADG in EW lambs from weeks 3 to 6 ( P = 0.041). Early weaning had negligible effects on duodenal morphology, organ, and carcass weights at weeks 4 and 16. Plasma metabolites (urea nitrogen, triglycerides, NEFA, glucose, and total protein) were similar between groups, while β-hydroxybutyrate was greater in EW than Ctrl lambs at weeks 4 and 6 ( P = 0.018) but not week 8 indicative of early rumen development. Serum IGF-1 tended to be lower in EW than Ctrl lambs from weeks 2 to 6 only ( P = 0.065). All lambs developed antibody responses postvaccination and there was no effect of treatment ( P = 0.528). The results of this study illustrate that artificially reared lambs can be weaned off MR by 4 or 6 wk of rearing without compromising growth, small intestine morphology, major organ development, and body composition, nor immune function at either 4 (preweaning) or 16 (postweaning) wk of age.